Impact of Russian economy deoffshorization on FDI inflows in the EAEU member countries - Sarkisyan, Erik; Bolotov, Ilya; Šváb, Patrik; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The thesis describes and analyzes the effects of Russian policies aimed at reducing capital flight to offshore zones, increasing tax transparency, and curbing financial capital round-tripping on the direct investment landscape in the EAEU member states. The direct investments are analyzed from the perspectives of total flows and investment stocks for each country before deoffshorization and after. The thesis is based on the assumption that economic integration and policy measures should have contributed to intra-regional investment flows increase.
Vedoucí práce: Ilya Bolotov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses